THE STATUS QUALITY WATER OF CIRCULATION COOLING WATER IN THE MELTING SCRAP FACTORY AND RECYCLING - Fian Surya Alif; Tugiyono Tugiyono; Agus Setiawan; Gregorius Nugroho Susanto (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2021)
Recycling metal scrap is an effort to save The earth from pollution, meanwhile in the process of recycling metal scrap usually it took a lot of water in the process to cooling it from such a high temperature. The purpose of this study was to identified water quality from the water in the reservoir and the water quality of the river that indicated receiving overflow from reservoir water when in the rainy season. The study was conducted from October to November 2020 at the Melting Scrap Factory and the river around the industrial zone. The study was conducted by taking a water sample for analysis in the spot (in-situ) and in the laboratory (ex-situ). The water sample was taken by a field technician laboratory. The result from laboratory analysis counted to indicate the water quality using Pollution Index methods (PI).and then in order to detect pollution from the fish that lived inside the pond using nutrition value coefficient (NVC). After the analysis data was counted the result showed that the water-saving pond had 3,20 values for pollution index(PI) and the river had 3,71 values for pollution index(PI), both of the results indicated that status water quality was classified as lightly polluted if it referred to the policy KEPMEN LH NO 11 Tahun 2003 for standard water quality class 3. Based on the data that has been counted for NVC the result was 1,84, it showed that the fish could live healthily but for further analysis laboratory on the fish meat, it showed that the fish meat was contained a high amount of a heavy metal compound such as iron (Fe) which had value over the standard (1953 mg/kg), from that value it showed how polluted the fishes in the reservoir. The fish should not be eaten by humans because of the high amount of heavy metal compound